Association between triglyceride-glucose and triglyceride glucose body mass index with risk of prediabetes: a multicenter Chinese medical examination cohort study - Feng, Chengya; Wang, Xinxing; Luo, Yanni (Frontiers in Endocrinology, 2025)
Background and aimsAlthough triglyceride-glucose (TyG) indices reliably identify insulin resistance and diabetes, their link to prediabetes risk is understudied. We analyze the associations of TyG and TyG-body mass index (TyG-BMI) with prediabetes risk in a Chinese population.MethodsThis retrospective cohort study used data from 11 urban physical-examination centers of the Rich Healthcare Group. A total of 161606 Chinese adults free of diabetes at baseline were included. Participants were categorized by quartiles of the TyG index and the TyG-BMI. Cox proportional hazards regression and Kaplan–Meier analyses were used to estimate the associations between these exposures and incident prediabetes. Restricted cubic splines with piecewise Cox models were applied to explore potential non-linear relationships and identify inflection points. Subgroup and sensitivity analyses were performed to assess the robustness of the findings.ResultsOver a median follow-up of 3.0 years, 18339 participants (11.3%) developed incident prediabetes. After multivariable adjustment, both TyG and TyG-BMI were positively associated with prediabetes risk. Restricted cubic splines revealed non-linear relationships (P < 0.001) with distinct threshold effects. The associations were stronger among adults younger than 45 years and among women, with significant additive interactions observed. Kaplan–Meier curves showed the highest cumulative incidence of prediabetes in the top quartiles of both TyG and TyG-BMI.ConclusionsIn this Chinese cohort, TyG and TyG-BMI showed non-linear associations with incident prediabetes, with steeper risk increases among women and adults younger than 45 years. These indices may identify high-risk insulin resistance states preceding dysglycemia.